Morphological and transcriptomic change of brain pericytes by lipopolysaccharide treatment - Asai, Taiki; Yonezu, Yoshino; Uyeda, Akiko; Watanabe, Haruki; Suzuki, Tatsunori; Misawa, Hidemi; Muramatsu, Rieko (Frontiers in Neural Circuits, 2026)
Brain pericytes play essential roles in vascular homeostasis, including capillary stabilization and maintenance of the blood–brain barrier. Lipopolysaccharide (LPS), a component of the outer membrane of Gram-negative bacteria, is known to trigger inflammatory responses not only systemically but also within the central nervous system. In this study, we investigated the effects of LPS on the phenotype and transcriptome of brain vascular pericytes. LPS promoted bromodeoxyuridine incorporation in the primary culture of human brain pericytes as well as increased the number of Ki67-positive cells, indicating enhanced pericyte proliferation. Morphological analysis revealed that LPS decreased the cellular aspect ratio, suggesting altered cellular elongation. Transcriptomic profiling showed that LPS-induced differentially expressed genes were enriched for terms related to cell proliferation, angiogenesis, and blood–brain barrier function. Because pericytes critically regulate neurovascular coupling and metabolic support for active neurons, these LPS-induced alterations may ultimately perturb the microvascular control of neural circuits. These results suggest that LPS has the potential to regulate brain vascular function by inducing morphological and functional changes in pericytes.